2019
DOI: 10.1103/physrevb.100.035112
|View full text |Cite
|
Sign up to set email alerts
|

Universal level statistics of the out-of-time-ordered operator

Abstract: The out-of-time-ordered correlator has been proposed as an indicator of chaos in quantum systems due to its simple interpretation in the semiclassical limit. In particular, its rate of possible exponential growth at → 0 is closely related to the classical Lyapunov exponent. Here we explore how this approach to quantum chaos relates to the random-matrix theoretical description. To do so, we introduce and study the level statistics of the logarithm of the out-of-time-ordered operator,Λ(t) = ln − [x(t),px(0)] 2 /… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 57 publications
3
54
0
Order By: Relevance
“…In quantum field theories we can upgrade (11) to the case where the operators are separated in space Cpt, xq " x´rV p0, 0q, W pt, xqs 2 y β .…”
Section: Probing Chaos With Local Operatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In quantum field theories we can upgrade (11) to the case where the operators are separated in space Cpt, xq " x´rV p0, 0q, W pt, xqs 2 y β .…”
Section: Probing Chaos With Local Operatorsmentioning
confidence: 99%
“…It was recently shown that the chaotic nature of many-body quantum systems can be diagnosed with certain out-of-time-order correlation (OTOC) functions which, in the gravitational description, are related to the collision of shock waves close to the black hole horizon [5][6][7][8][9]. In addition to being useful for diagnosing chaos in holographic systems and providing a deeper understanding for the inner-working mechanisms of gauge-gravity duality, OTOCs have also proved useful in characterizing chaos in more general non-holographic systems, including some simple models like the kicked-rotor [10], the stadium billiard [11], and the Dicke model [12].…”
Section: Introductionmentioning
confidence: 99%
“…The more traditional approach to quantum chaos, however, focuses on the properties of the spectrum and uses level statistics as in random matrix theory (RMT) as its main signature [10][11][12][13]. There are several examples of cases where a correspondence between the exponential growth of the OTOC and level repulsion as in RMT has been found [14][15][16][17][18], but exceptions also exist [19][20][21]. In the present work, we propose a way to directly detect the effects of level repulsion in the evolution of a quantum system.…”
Section: Introductionmentioning
confidence: 99%
“…The quantum-classical correspondence between the exponential growth rate of the OTOC and the classical Lyapunov exponent has being numerically corroborated for finite systems with few degrees of freedom, such as one-body chaotic systems [27,28] and the Dicke model with two degrees of freedom [29]. However, little is known about this correspondence for finite quantum systems with many interacting particles.…”
Section: Introductionmentioning
confidence: 99%